Bioethics and patient autonomy: how far does the professional’s decision go? – Literature review (Research, Society and Development, 2025)
Introduction: Deontology ("Deontos": duty and "Logos": knowledge), a branch of ethics conceived by Jeremy Betham, constitutes obligations or recommendations for the best professional practice, in addition to legal obligations, regardless of religious or doctrinal orientations. Relationships and behaviors have ideas, principles and values ​​that are permeated by ethics. In view of this, bioethics is among the ethical principles for life. Bioethics therefore presents a comprehensive field. It designates a set of ethical issues that bring into play important values ​​for humanity due to the increasing power of techno-scientific intervention in living beings, especially in humans. Objective: The present study aims to discuss the limits of this autonomy and to what extent the professional can or should intervene. Methodology: This work is a qualitative literature review, with an exploratory nature and bibliographic design, carried out from searches carried out between 2020 and 2025. The data collection applied in this study was developed through academic research found through searches on academic-scientific websites such as the Brazilian Digital Library of Theses and Dissertations (BDTD), PubMed, LILACS and SciELO. Results: The theoretical analysis carried out throughout the present study demonstrated that, although patient autonomy is a widely recognized ethical and legal principle, its practical application encounters relevant limits in the clinical context. Conclusion: Patient autonomy is an essential pillar of bioethics, but it is not absolute.